Three Sports Complexes in Irkutsk and Shelekhov - Pilipenko, Anastasia (project baikal, 2017)
The article tells about the sports facilities that have been worked out by the Siberian Design Institute in Irkutsk and Shelekhov within the last three years. The team of authors has designed three sports complexes for different kinds of sports in the unique urban context. While designing the facilities of such different shapes and volumes, the architects kept to the same principles of careful attitude toward context, maximal efficiency of spatial organization, and application of a wide range of modern materials.
Keywords: Siberian Design Institute; sports; multifunctional sports center; visualization of the building